Association of COVID-19 with impaired endothelial glycocalyx, coronary flow and longitudinal strain four months after infection. (4th February 2022) - Ikonomidis, I; Katogiannis, K; Mitrakou, A; Kountouri, A; Thymis, J; Korakas, E; Varlamos, C; Andreadou, I; Tsoumani, M; Bamias, A; Kazakou, P; Grigoropoulou, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: SARS-CoV-2 infection may lead to endothelial and vascular dysfunction. We investigated alterations of arterial stiffness, endothelial coronary and myocardial function markers four months after COVID-19 infection. Methods: In a case-control prospective study, we included 100 patients four months after COVID-19 infection, 50 age- and sex-matched healthy individuals. We measured a) perfused boundary region (PBR) of the sublingual arterial microvessels (increased PBR indicates reduced endothelial glycocalyx thickness), b) flow-mediated dilation (FMD), c) coronary Flow Reserve (CFR) by Doppler echocardiography d) pulse wave velocity (PWV) e) global left (LV) and right (RV) ventricular longitudinal strain (GLS), f) malondialdehyde (MDA), an oxidative stress marker, von-Willenbrand factor and thrombomodulin as endothelial biomarkers. Results: COVID-19 patients had lower CFR and FMD values than controls (2.39 ± 0.39 vs 3.31 ± 0.59, p = 0.0122, 5.12 ± 2.95% vs 8.12 ± 2.23%, p = 0.006 respectively). Compared to controls, COVID-19 had greater PBR5-25 (2.11 ± 0.14μm vs 1.87 ± 0.16μm, p = 0.002), higher PWV (PWVc-f 12.32 ± 2.44 vs 10.11 ± 1.85 m/sec, p = 0.033) and impaired LV and RV GLS (-19.11 ± 2.14% vs -20.41 ± 1.61%, p = 0.001 and -16.45 ± 3.33% vs -20.11 ± 2.48%, p < 0.001). MDA and thrombomodulin were higher in COVID-19 patients than controls (10.55 ± 2.45 vs 1.01 ± 0.50 nmole/L, p = 0.001 and 3716.63 ± 188.36 vs 2590.02 ± 156.51pg/ml, p < 0.001). Residual cardiovascular symptoms at 4 months were associated with oxidative stress and endothelial dysfunction markers. Conclusions: SARS-CoV-2 may cause endothelial and vascular dysfunction linked to impaired cardiac performance four months after infection.